Speech Acts on McDonald’s Slogans and/or Headlines in Written Advertisements - Stefany Juliwati (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study of speech act was to find out about the illocutionary functions and the relationship between structural form and its communicative function. The source of the data is 24 written advertisements as published in the website Bored Panda. The data of this study are the 34 slogans and/or headlines found in the selected 24 McDonald’s’ written advertisements. The writer used qualitative approach. The theories applied consist of speech act, context and modes, body language, and copywriting. The findings reveal that regarding illocutionary functions, representatives serve as the most frequent type, followed by expressives and directives. The absence of comissives indicates that using promises/threats to promote is not a good promotional strategy. Meanwhile, the absence of declarations indicates the copywriters’ non-existent institutional roles to perform the act. All (34 out of 34) the speech acts have direct relationship between the structural form and communicative function.Keywords: speech acts, slogans, headlines, advertisements.